2016
DOI: 10.5604/17322693.1209210
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s disease against peptides products of enzymatic cleavage of APP protein. Forming and variety of fibrillating peptides – some aspects

Abstract: Various and different peptides products resulting from enzymatic protein cleavage of Amyloid Precursor Proteins (APP) are the main agents in the pathophysiology of Alzheimer's disease (AD). Although relatively well-known, they still arouse interest leading to further intense and wide-ranging research. Their biology and physico-chemical properties still are challenging for basic, experimental research and are matter of scientific debate. The APP itself and its functions are still somewhat enigmatic and therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…ALC stimulates α-secretase activity and physiological amyloid precursor protein (APP) metabolism. In particular, ALC favors the delivery of disintegrin and metalloproteinase domain-containing protein 10 (ADAM10), the most accredited α-secretase, to the post-synaptic compartment and, consequently, positively modulates ADAM10’s enzymatic activity toward APP [ 76 ]. Palmitoylcarnitine (ester of carnitine with palmitic acid) can stimulate the expression of GAP-43 (also named B-50, neuromodulin, F1, pp45), a protein involved in neural development, neuroplasticity and neurotransmission [ 77 ].…”
Section: Physiological Properties Of L-carnitinementioning
confidence: 99%
“…ALC stimulates α-secretase activity and physiological amyloid precursor protein (APP) metabolism. In particular, ALC favors the delivery of disintegrin and metalloproteinase domain-containing protein 10 (ADAM10), the most accredited α-secretase, to the post-synaptic compartment and, consequently, positively modulates ADAM10’s enzymatic activity toward APP [ 76 ]. Palmitoylcarnitine (ester of carnitine with palmitic acid) can stimulate the expression of GAP-43 (also named B-50, neuromodulin, F1, pp45), a protein involved in neural development, neuroplasticity and neurotransmission [ 77 ].…”
Section: Physiological Properties Of L-carnitinementioning
confidence: 99%
“…Proteolytic cleavage of amyloid precursor polypeptide chain by secretases (mainly β- and γ-secretase) produces Aβ40 and Aβ42 peptides, which consist of 40 and 42 amino acids, respectively. The latter one, due to its hydrophobicity, is characterized by a greater tendency to form fibrils and is believed to be the main factor responsible for the formation of amyloid deposits [ 55 ]. However, Nagababu et al suggested that the enhanced toxic effect observed for Aβ42 could be attributed to a greater toxicity of the 1–42 aggregates than the 1–40 ones of a comparable size distribution and not to the formation of larger fibrils [ 56 ].…”
Section: Role Of Vitamin C In Neurodegenerative Diseasesmentioning
confidence: 99%
“…In healthy individuals, the concentration of Aβ 42 is in the range of 600-890 pg/mL. In the initial stage of AD, the concentration decreases to 445-614 pg/mL, which can be observed many years before the appearance of clinical symptoms of the disease [116,117]. In the brain of people with AD, Aβ 42 is the main peptide found in amyloid plaques.…”
Section: Diagnostic and Potential Ad Biomarkers From Cerebrospinal Fluidmentioning
confidence: 99%